AN ANALYSIS OF SEMANTIC DEVIATION IN MAROON 5'S SONG LYRICS IN ALBUM V - Gina Anggraeni; M. Bahri Arifin; Famala Eka Sanhadi Rahayu (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
ABSTRACT Song lyric is a literary work that contains the outpouring of personal feelings, emotions, and expressions of soul-shaped experiences in the form of the composition of words in a song. This finding is qualitative research using stylistic approach, which aims to identify types and functions of semantic deviation found in Maroon 5 song in album V. The utilized theories in this research are semantic deviation by Heinrich F. Plett (2010) and Laurence Perrine (1963). The data were lines which contained semantic deviations in Maroon 5 song in album V. The results of the research are as follows. First, eight out of twelve types of semantic deviation, there are in Maroon 5 song in album V, namely: 1) pleonasm, 2) oxymoron, 3) metaphor, 4) irony, 5) simile, 6) hyperbole, 7) paradox, and 8) litotes. Metaphor is the prominent type used in this work. This finding indicates that the songwriter tends to deliver his ideas through some comparisons. It is because metaphor gives the broadest freedom for creativity, but it also looks interesting. Second, there are four functions found, i.e: 1) to bring additional imaginary, 2) to add emotional intensity, 3) to afford imaginative pleasure, and 4) to say much in brief compass. To bring additional imaginary is the dominant function. This is because Adam Levine has the tendency to make his song lyrics by using interesting expression, and it imagined as if it was real.Keywords: stylistics, semantic deviation, Maroon 5 album V ABSTRAK Lirik lagu merupakan karya sastra yang berisi curahan perasaan pribadi, emosi, dan ekspresi pengalaman berbentuk jiwa berupa susunan kata-kata dalam sebuah lagu. Temuan ini adalah penelitian kualitatif dengan pendekatan stilistika, yang bertujuan untuk mengidentifikasi jenis dan fungsi deviasi semantik yang terdapat pada lagu Maroon 5 di album V. Teori yang digunakan dalam penelitian ini adalah penyimpangan semantik oleh Heinrich F. Plett (2010) dan Laurence Perrine (1963). Data berupa baris-baris yang mengandung penyimpangn semantik pada lagu Maroon 5 album V. Hasil penelitian adalah sebagai berikut. Pertama, delapan dari dua belas jenis penyimpangan semantik terdapat pada lagu Maroon 5 di album V, yaitu: 1) pleonasm, 2) oxymoron, 3) metafora, 4) ironi, 5) simile, 6) hiperbola, 7) paradoks , dan 8) litotes. Metafora adalah tipe utama yang digunakan dalam karya ini. Temuan ini menunjukkan bahwa penulis lagu cenderung menyampaikan idenya melalui beberapa perbandingan. Karena metafora memberikan kebebasan seluas-luasnya untuk berkreasi, tetapi juga terlihat menarik. Kedua, ada empat fungsi yang ditemukan, yaitu: 1) untuk membawa tambahan imajiner, 2) untuk menambahkan intensitas emosional, 3) untuk membeli kesenangan imajinatif, dan 4) untuk mengatakan banyak di kompas singkat. Untuk membawa imajiner tambahan adalah fungsi yang dominan. Hal ini karena Adam Levine memiliki kecenderungan membuat lirik lagunya dengan ekspresi yang menarik, dan dibayangkan seolah-olah nyata.Kata Kunci: stilistik, penyimpangan semantic, Maroon 5 album V